Exploring the Parameters of Verb Agreement in Majhi - Dhakal, Dubi Nanda (Gipan, 2017)
This paper discusses a number of parameters which trigger verb agreement in Majhi, an Indo-Aryan language spoken in Nepal. Like some Indo-Aryan neighbours, Majhi takes account of ranges of facts in the verb agreement. The verb is not only marked for agreement with one nominal phrase in a clause, but also encodes inflectional features of both subject and object simultaneously in transitive and ditransitive verbs by employing portmanteau suffixes. The features that control the agreement include person, number, honorificity, gender, and case roles of nouns.